Layered heterostructured silicon carbide skeleton-titanium-based amorphous composite material and preparation thereof

CN120396454BActive Publication Date: 2026-10-20NORTHEASTERN UNIV CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510564235.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-04-30
Publication Date
2026-10-20
Estimated Expiration
2045-04-30

AI Technical Summary

Technical Problem

[0004]针对上述问题,本发明的目的在于提供一种层状异构碳化硅骨架-钛基非晶复合材料及其制备方法,以解决碳化硅陶瓷断裂韧性差的问题

Benefits of technology

[0024]本发明以碳化硅网状多孔层、纯钛网状多孔层和碳化硅单片层交替叠层为三维骨架结构体,进而设计构建了三维骨架结构与钛基BMGs交替叠层的复合材料体系,具有较好的强度与断裂韧性。本发明的层状异构碳化硅骨架-钛基非晶复合材料在实现抗压强度与断裂韧性优异匹配的同时,显著降低了对早期裂纹的敏感性,有效地扩宽了碳化硅陶瓷在高技术领域广阔的应用前景。其中,层状异构碳化硅骨架结构展现出新颖高效的设计理念。成型过程中通过引入聚氨酯网络基底,能够构建熔渗通道以提升钛基非晶合金在碳化硅骨架中的渗透效率,并且碳化硅和纯钛粉体的添加不仅有助于增强结构稳定性,更对优化孔隙率与连通性具有关键作用,这对熔渗工艺至关重要,为制备高性能碳化硅复合材料提供了新思路。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120396454B_ABST
    Figure CN120396454B_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of silicon carbide composite material, and particularly relates to a layered isomeric silicon carbide skeleton-titanium-based amorphous composite material and a preparation method thereof. The silicon carbide ceramic has the problem of poor fracture toughness. The composite material provided by the present application is composed of a layered isomeric silicon carbide skeleton and a titanium-based amorphous alloy. The present application successfully prepares thin-layer silicon carbide flake bodies by using a polycarbosilane precursor conversion method, and combines the thin-layer silicon carbide flake bodies with a porous silicon carbide network layer or a porous titanium network layer to prepare an excellent three-dimensional layered isomeric silicon carbide skeleton. The layered isomeric silicon carbide skeleton-titanium-based amorphous composite material is prepared by a melting infiltration process. The composite material simultaneously exhibits excellent compressive strength and fracture toughness. The layered structure can effectively inhibit strain localization, thereby reducing the crack tip stress intensity factor and crack propagation driving force, and significantly reducing the sensitivity to early cracks.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of silicon carbide composite material technology, and specifically relates to a layered heterogeneous silicon carbide framework-titanium-based amorphous composite material and its preparation. Background Technology

[0002] Silicon carbide (SiC) ceramics, due to their low thermal conductivity, excellent chemical stability, and high-temperature specific strength, have demonstrated significant application value in aerospace, nuclear energy, and high-temperature energy conversion devices. However, the high brittleness caused by the strong covalent Si-C bonds in SiC ceramics makes them extremely sensitive to structural defects. To address the shortcomings of single-phase SiC's low fracture toughness and high defect sensitivity, researchers have successively developed various toughening composite materials, including fiber-reinforced composites, phase transformation component composites, and ductile metal introductions, and proposed toughening mechanisms such as whisker / fiber pull-out bridging, stress-induced plastic phase transformation, matrix / reinforcement interface dissociation, and crack deflection. Among these, SiC-metal composites exhibit the most significant overall toughening effect, but their preparation process is relatively complex.

[0003] In metallic systems suitable for SiC composites, titanium-based bulk metallic glasses (BMGs) exhibit significantly high strength and hardness due to their amorphous structure (lacking grain boundaries, dislocations, and other crystal defects), with their plastic deformation primarily relying on highly localized shear bands. When combined with SiC, titanium-based BMGs effectively improve the toughness of the composite while maintaining high specific strength, and their lower melting point effectively inhibits the formation of harmful interfacial reaction products during the composite process. For brittle composites, the two-phase microstructure has a crucial impact on toughness: two-phase structures lacking mutual restraint often exhibit weak crack propagation resistance, and microcracks easily evolve into unsteady master cracks, leading to early fracture. Therefore, suppressing the development of unsteady critical master cracks is a core challenge in improving mechanical properties. Introducing layered structures is considered an effective toughening approach; for example, Ti-Al3Ti layered composites, by introducing Ti layers, improve their toughness by an order of magnitude compared to single-phase Al3Ti. Although existing studies have shown that layered structures can effectively avoid strain localization problems, systematic research on SiC-metal layered composites is still lacking, and their deep toughening mechanism needs to be explored in depth. Summary of the Invention

[0004] To address the above problems, the present invention aims to provide a layered heterogeneous silicon carbide framework-titanium-based amorphous composite material and its preparation method, so as to solve the problem of poor fracture toughness of silicon carbide ceramics.

[0005] The technical solution of this invention is as follows:

[0006] The present invention discloses a layered heterogeneous silicon carbide framework-titanium-based amorphous composite material, which is composed of a silicon carbide framework and a titanium-based amorphous alloy, wherein the titanium-based amorphous alloy is infiltrated and embedded in the silicon carbide framework; the silicon carbide framework is a multilayer heterogeneous structure, consisting of at least one of silicon carbide mesh porous layers and pure titanium mesh porous layers, alternately stacked with silicon carbide monolayers; the silicon carbide framework contains silicon carbide particles with a particle size of 500 nm to 50 μm or titanium particles with a particle size of 1 μm to 50 μm.

[0007] The method for preparing a layered heterogeneous silicon carbide framework-titanium-based amorphous composite material according to the present invention includes the following:

[0008] A silicon carbide skeleton and a titanium-based amorphous alloy are placed in a mold. The titanium-based amorphous alloy is first heated in a vacuum environment to become molten. Then, pressure is applied to allow the molten titanium-based amorphous alloy to infiltrate and embed into the silicon carbide skeleton, resulting in a layered heterogeneous silicon carbide skeleton-titanium-based amorphous composite material.

[0009] The silicon carbide framework is a multi-layered heterogeneous structure, consisting of at least one of silicon carbide mesh porous layers and pure titanium mesh porous layers, alternately stacked with silicon carbide monolayers.

[0010] The preparation method of the layered heterogeneous silicon carbide framework-titanium-based amorphous composite material includes the following specific contents:

[0011] A silicon carbide framework and a titanium-based amorphous alloy were placed in a mold at 10... -3 Pa~10 -4 Heating to 860℃~950℃ under vacuum to molten state of titanium-based amorphous alloy, and then holding at 0.3MPa~0.5MPa pressure for 10 minutes~15 minutes to allow the molten titanium-based amorphous alloy to infiltrate and embed into the silicon carbide skeleton. After water quenching and cooling, the layered heterogeneous silicon carbide skeleton-titanium-based amorphous composite material is finally obtained.

[0012] The method for preparing the silicon carbide framework is as follows:

[0013] At least one of a single-layer silicon carbide mesh porous layer and a single-layer pure titanium mesh porous layer is alternately stacked with a single-layer silicon carbide monolayer to form a three-dimensional skeleton structure; the silicon carbide skeleton is obtained after thermal crosslinking treatment, pyrolysis treatment and densification treatment.

[0014] The thermal crosslinking treatment refers to holding the temperature at 180℃~220℃ for 4 to 6 hours;

[0015] The pyrolysis treatment refers to heating to 850℃ to 1200℃ in an argon atmosphere of 0.2MPa to 0.4MPa at a rate of 8℃ / min to 12℃ / min, and holding at that temperature for 1 hour to 2 hours.

[0016] The densification treatment refers to hot isostatic pressing (HIP) treatment at 1200℃~1400℃ and 80MPa~100MPa for 1 hour to 2 hours.

[0017] The method for preparing the single-layer silicon carbide monolayer is as follows:

[0018] Silicon carbide powder and liquid polycarbosilane are mixed into a slurry, and the silicon carbide monolayer is obtained after molding; the mass fraction of silicon carbide powder in the mixed slurry is 80%, and the thickness of the silicon carbide monolayer is 100μm to 400μm.

[0019] The method for preparing the single-layer silicon carbide mesh porous layer is as follows:

[0020] Silicon carbide powder and polyvinyl alcohol (PVA) are dispersed in deionized water to prepare an aqueous slurry M, which is then molded in a mesh substrate to obtain the silicon carbide mesh porous layer. The mass fraction of silicon carbide powder in the aqueous slurry M is 20% to 35%, and the mass fraction of polyvinyl alcohol is 10% to 15%. The mesh substrate is a polyurethane mesh with a pore size of 80 μm to 150 μm, and the thickness of the silicon carbide mesh porous layer is 100 μm to 300 μm.

[0021] The method for preparing the single-layer pure titanium mesh porous layer is as follows:

[0022] Aqueous slurry N is prepared by dispersing titanium powder and polyvinyl alcohol in deionized water, and then formed in a mesh substrate to obtain the pure titanium mesh porous layer. The mass fraction of pure titanium powder in the aqueous slurry N is 20% to 35%, and the mass fraction of polyvinyl alcohol is 10% to 15%. The mesh substrate is a polyurethane mesh with a pore size of 80 μm to 150 μm, and the thickness of the pure titanium mesh porous layer is 100 μm to 300 μm.

[0023] Compared with existing materials and technologies, the present invention has the following advantages and beneficial effects:

[0024] This invention utilizes an alternating layering of silicon carbide mesh porous layers, pure titanium mesh porous layers, and silicon carbide monolayers as a three-dimensional framework structure. A composite material system combining this three-dimensional framework structure with alternating titanium-based BMGs (Body Metal Magnets) layers is then designed and constructed, exhibiting good strength and fracture toughness. This layered heterogeneous silicon carbide framework-titanium-based amorphous composite material achieves an excellent match between compressive strength and fracture toughness while significantly reducing sensitivity to early cracking, effectively broadening the application prospects of silicon carbide ceramics in high-tech fields. The layered heterogeneous silicon carbide framework structure demonstrates a novel and efficient design concept. During the molding process, the introduction of a polyurethane network substrate enables the construction of infiltration channels to improve the infiltration efficiency of titanium-based amorphous alloys within the silicon carbide framework. Furthermore, the addition of silicon carbide and pure titanium powder not only enhances structural stability but also plays a crucial role in optimizing porosity and connectivity, which is essential for the infiltration process and provides a new approach for preparing high-performance silicon carbide composite materials. Attached Figure Description

[0025] Figure 1 This is a schematic diagram of the preparation process of the layered heterogeneous silicon carbide framework-titanium-based amorphous composite material of the present invention; wherein: (a) is Example 1, (b) is Example 2.

[0026] Figure 2 This is a cross-sectional scanning electron micrograph of the layered heterogeneous silicon carbide framework in Example 1.

[0027] Figure 3 The images shown are scanning electron micrographs of the microstructure of the composite material in Example 1; where (a) and (b) are both scanning electron micrographs of the cross-section of the composite material.

[0028] Figure 4 This is a cross-sectional scanning electron micrograph of the layered heterogeneous silicon carbide framework in Example 2.

[0029] Figure 5 The images shown are scanning electron micrographs of the microstructure of the composite material in Example 2; where (a) and (b) are both cross-sectional scanning electron micrographs.

[0030] Figure 6 The images show the compression mechanics curves and macroscopic fracture photographs of the composite materials of Examples 1 and 2; where: (a) is the compression mechanics curve; (b) is the macroscopic fracture photograph in the parallel direction of Example 2; (c) is the macroscopic fracture photograph in the perpendicular direction of Example 2; (d) is the macroscopic fracture photograph in the parallel direction of Example 1; and (e) is the macroscopic fracture photograph in the perpendicular direction of Example 1.

[0031] Figure 7 The diagram shows the fracture finite element simulation analysis of the composite material in Example 1; where (a) represents the vertical direction and (b) represents the parallel direction.

[0032] Figure 8 The images are scanning electron micrographs of the fracture morphology of the composite materials in Examples 1 and 2; where: (a) is the direction parallel to Example 2, (b) is the direction perpendicular to Example 2; (c) is the direction parallel to Example 1, and (d) is the direction perpendicular to Example 1.

[0033] Figure 9 The image shows the fracture toughness test curve of the composite material in Example 1.

[0034] Figure 10 The images shown are scanning electron micrographs of the fracture surface morphology of the composite material in Example 1; where: (a) is the fracture surface when the notch is located in the amorphous alloy phase, and (b) is the fracture surface when the notch is located in the silicon carbide phase.

[0035] Figure 11 The image shows the fracture toughness test curve of the composite material in Example 2.

[0036] Figure 12 The images shown are scanning electron micrographs of the fracture surface morphology of the composite material in Example 2; where (a) is the fracture surface when the notch is located in the amorphous alloy phase, and (b) is the fracture surface when the notch is located in the silicon carbide phase.

[0037] Figure 13 This is a cross-sectional scanning electron micrograph of the composite material of Example 3.

[0038] Figure 14 This is a cross-sectional scanning electron micrograph of the composite material of Example 4.

[0039] Figure 15 This is a cross-sectional scanning electron micrograph of the composite material of Example 5.

[0040] Figure 16 This is a cross-sectional scanning electron micrograph of the composite material of Example 6.

[0041] Figure 17 This is a cross-sectional scanning electron micrograph of the composite material in Comparative Example 1.

[0042] Figure 18 This is a cross-sectional scanning electron micrograph of the composite material in Comparative Example 2.

[0043] Figure 19 This is a cross-sectional scanning electron micrograph of the composite material in Comparative Example 3. Detailed Implementation

[0044] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments and accompanying drawings. It should be noted that the embodiments described in this invention are only for further explanation and illustration, and not for limiting their application scope. Based on this invention, all other embodiments obtained by those skilled in the art without inventive effort are within the protection scope of this invention.

[0045] Unless otherwise specified, the silicon carbide particles used in this invention have a particle size of 500 nm to 50 μm, the titanium particles have a particle size of 1 μm to 50 μm, and a purity of 99% to 99.99%. The curing temperature of the liquid polycarbosilane is 130°C to 180°C. The titanium-based amorphous alloy is a Ti32.8Zr30.2Ni5.3Cu9Be22.7 (ZT3, at.%) titanium-based bulk amorphous alloy ingot. The slurry molding temperature is 40°C. The composite material prepared in the embodiments of this invention comprises a 75% layered heterogeneous silicon carbide framework and a 25% titanium-based amorphous alloy by volume. The composite material has a dense structure and is essentially non-porous.

[0046] Example 1

[0047] In this layered heterogeneous silicon carbide framework-titanium-based amorphous composite material, the silicon carbide framework is composed of alternating layers of silicon carbide monolayers and silicon carbide network porous layers, and the silicon carbide framework contains silicon carbide particles with a particle size of 50 μm.

[0048] The specific preparation process of the composite material is as follows:

[0049] Layered heterogeneous silicon carbide framework and titanium-based bulk amorphous alloy ingot are placed in a mold and then subjected to 10... -3 Heating to 860℃ under vacuum at 0.4 MPa molten state, the titanium-based amorphous alloy was molten. Then, infiltration was performed at 0.4 MPa pressure to embed the molten titanium-based amorphous alloy into the silicon carbide framework. After holding at this temperature for 15 minutes, water quenching was performed to obtain a layered heterogeneous silicon carbide framework-titanium-based amorphous composite material. Its cross-sectional scanning electron micrograph is shown below. Figure 3 (a) and Figure 3 As shown in (b). The preparation process is as follows: Figure 1 As shown in (a).

[0050] The preparation method of the layered heterogeneous silicon carbide framework is as follows:

[0051] A three-dimensional framework structure was constructed by alternately stacking monolayer silicon carbide sheets and monolayer silicon carbide mesh porous layers. First, a thermal cross-linking treatment was performed at 200℃ for 4 hours. Then, a pyrolysis treatment was carried out in an argon atmosphere at 0.4 MPa, with the temperature increased to 1000℃ at a rate of 10℃ / min and held for 1 hour. Finally, a hot isostatic pressing (HIP) densification treatment was performed at 1400℃ and 100 MPa for 1 hour to obtain a densified layered heterogeneous silicon carbide framework. The cross-sectional scanning electron micrograph is shown below. Figure 2 As shown (the inset is a magnified view of a portion).

[0052] The preparation method of a single-layer silicon carbide monolayer is as follows:

[0053] Silicon carbide powder and liquid polycarbosilane were mixed into a slurry, with the mass fraction of silicon carbide powder being 80%. After molding, a silicon carbide monolayer was obtained with a thickness of 100 μm.

[0054] The preparation method of a single-layer silicon carbide mesh porous layer is as follows:

[0055] Silicon carbide powder and polyvinyl alcohol were dispersed in deionized water to prepare an aqueous slurry. The aqueous slurry contained 30% silicon carbide powder with a particle size of 50 μm and 10% polyvinyl alcohol. A 200 μm thick mesh film, namely silicon carbide mesh porous layer, was obtained by molding a polyurethane mesh with a pore size of 100 μm as a substrate.

[0056] When the lamellar direction of the composite material is parallel to the load (ZT3 / SiC hor), the strength of the composite material is lower than that when the lamellar direction is perpendicular to the load (ZT3 / SiC ver approximately 1485 MPa), such as Figure 6 As shown in (a), macroscopic photographs of the fracture of the composite material in the parallel and perpendicular directions are as follows. Figure 6 (d) and Figure 6 As shown in (e). Figure 8 (c) and Figure 8 (d) reveals a hybrid failure mode, which includes both interlaminar peeling and intralaminar cracking. Figure 7 (a) and Figure 7 (b) illustrates the compressive stress variation of the layered composite material in different directions. Importantly, the composite material prepared in this invention exhibits not only high mechanical strength but also excellent fracture toughness. The fracture toughness test results are as follows: Figure 9 As shown, the fracture toughness is 16.4 MPa·m when the notch is located in the amorphous alloy phase. 1 / 2 ,like Figure 10 As shown in (a); when the notch is located in the silicon carbide phase, the fracture toughness is 12.4 MPa·m. 1 / 2 ,like Figure 10 As shown in (b), the structure designed with composite materials significantly reduces susceptibility to early cracking.

[0057] Example 2

[0058] In this layered heterogeneous silicon carbide framework-titanium-based amorphous composite material, the silicon carbide framework is composed of alternating layers of silicon carbide monolayers and pure titanium mesh porous layers, and the silicon carbide framework contains titanium particles with a particle size of 50 μm.

[0059] The specific preparation process of the composite material is as follows:

[0060] Layered heterogeneous silicon carbide framework and titanium-based bulk amorphous alloy ingot are placed in a mold and then subjected to 10... -3 Heating to 860℃ under vacuum at 0.4 MPa molten state, the titanium-based amorphous alloy was molten. Then, infiltration was performed at 0.4 MPa pressure to embed the molten titanium-based amorphous alloy into the silicon carbide framework. After holding at this temperature for 15 minutes, water quenching was performed to obtain a layered heterogeneous silicon carbide framework-titanium-based amorphous composite material. Its cross-sectional scanning electron micrograph is shown below. Figure 5 (a) and Figure 5 As shown in (b). The preparation process is as follows: Figure 1 As shown in (b).

[0061] The preparation method of the layered heterogeneous silicon carbide framework is as follows:

[0062] A three-dimensional framework structure was constructed by alternately stacking monolayers of silicon carbide and monolayers of pure titanium mesh containing titanium particles. First, a thermal cross-linking treatment was performed at 200℃ for 4 hours. Then, a pyrolysis treatment was carried out in an argon atmosphere at 0.4 MPa, with the temperature increased to 1000℃ at a rate of 10℃ / min and held for 1 hour. Finally, a densification treatment was performed by hot isostatic pressing (HIP) at 1400℃ and 100 MPa for 1 hour, resulting in a densified layered heterogeneous silicon carbide framework. The cross-sectional scanning electron micrograph is shown below. Figure 4 As shown (the inset is a magnified view of a portion).

[0063] The preparation method of a single-layer silicon carbide monolayer is as follows:

[0064] Silicon carbide powder and liquid polycarbosilane were mixed into a slurry, with the mass fraction of silicon carbide powder being 80%. After molding, a silicon carbide monolayer was obtained with a thickness of 100 μm.

[0065] The preparation method of a single-layer pure titanium mesh porous layer is as follows:

[0066] Pure titanium powder and polyvinyl alcohol were dispersed in deionized water to prepare an aqueous slurry. The aqueous slurry contained 30% pure titanium powder with a particle size of 50 μm and 10% polyvinyl alcohol. A 200 μm thick mesh film, namely a pure titanium mesh porous layer, was obtained by molding a polyurethane mesh with a pore size of 100 μm as a substrate.

[0067] When the lamellar direction of the composite material is parallel to the load (ZT3(Ti) / SiC hor), the strength of the composite material is lower than that when the lamellar direction is perpendicular to the load (ZT3(Ti) / SiC ver approximately 1600 MPa), such as Figure 6 As shown in (a), macroscopic photographs of the fracture of the composite material in the parallel and perpendicular directions are as follows. Figure 6 (b) and Figure 6 As shown in (c). Figure 8 (a) and Figure 8 (b) A hybrid failure mode was revealed, involving both interlaminar delamination and intralaminar cracking. Importantly, the layered heterogeneous silicon carbide framework / titanium-based amorphous composite material containing titanium particles prepared in this invention exhibits not only high mechanical strength but also excellent fracture toughness. When the notch is located in the amorphous alloy phase, the fracture toughness is 26.1 MPa·m. 1 / 2 ,like Figure 12 As shown in (a); when the notch is located in the silicon carbide phase, the fracture toughness is 19.7 MPa·m. 1 / 2 ,like Figure 12 As shown in (b), the structure designed with composite materials significantly reduces susceptibility to early cracking.

[0068] Example 3

[0069] In this layered heterogeneous silicon carbide framework-titanium-based amorphous composite material, the silicon carbide framework is composed of alternating layers of silicon carbide monolayers and silicon carbide mesh porous layers, and the silicon carbide framework contains silicon carbide particles with a particle size of 500 nm.

[0070] The specific preparation process of the composite material is as follows:

[0071] Layered heterogeneous silicon carbide framework and titanium-based bulk amorphous alloy ingot are placed in a mold and then subjected to 10... -3 Heating to 950℃ under vacuum at 0.5 MPa molten state, the titanium-based amorphous alloy was molten. Then, infiltration was performed at 0.5 MPa pressure to embed the molten titanium-based amorphous alloy into the silicon carbide framework. After holding at this temperature for 10 minutes, water quenching was performed to obtain a layered heterogeneous silicon carbide framework-titanium-based amorphous composite material. Its cross-sectional scanning electron micrograph is shown below. Figure 13 As shown.

[0072] The preparation method of the layered heterogeneous silicon carbide framework is as follows:

[0073] A three-dimensional framework structure was formed by alternately stacking monolayer silicon carbide sheets and monolayer silicon carbide mesh porous layers. First, it was subjected to thermal cross-linking treatment at 220℃ for 6 hours. Then, it was subjected to pyrolysis treatment by heating to 1200℃ at 12℃ / min in an argon atmosphere of 0.3MPa and holding for 2 hours. Finally, it was subjected to densification treatment by hot isostatic pressing (HIP) at 1300℃ and 90MPa for 2 hours to obtain a densified layered heterogeneous silicon carbide framework.

[0074] The preparation method of a single-layer silicon carbide monolayer is as follows:

[0075] Silicon carbide powder and liquid polycarbosilane were mixed into a slurry, with the mass fraction of silicon carbide powder being 80%. After molding, a silicon carbide monolayer was obtained with a thickness of 400 μm.

[0076] The preparation method of a single-layer silicon carbide mesh porous layer is as follows:

[0077] Silicon carbide powder and polyvinyl alcohol were dispersed in deionized water to prepare an aqueous slurry. The aqueous slurry contained 35% silicon carbide powder with a particle size of 500 nm and 15% polyvinyl alcohol. A 300 μm thick mesh film, i.e., a silicon carbide mesh porous layer, was obtained by molding a polyurethane mesh with a pore size of 150 μm as a substrate.

[0078] The layered heterogeneous silicon carbide framework-titanium-based amorphous composite material prepared in this embodiment has a maximum compressive strength of approximately 1400 MPa. When the notch is located in the amorphous alloy phase, the fracture toughness is 15.3 MPa·m. 1 / 2 When the notch is located in the silicon carbide phase, the fracture toughness is 11.0 MPa·m. 1 / 2 .

[0079] Example 4

[0080] In this layered heterogeneous silicon carbide framework-titanium-based amorphous composite material, the silicon carbide framework is composed of alternating layers of silicon carbide monolayers and pure titanium mesh porous layers, and the silicon carbide framework contains titanium particles with a particle size of 1μm.

[0081] The specific preparation process of the composite material is as follows:

[0082] Layered heterogeneous silicon carbide framework and titanium-based bulk amorphous alloy ingot are placed in a mold and then subjected to 10... -3 Heating to 950℃ under vacuum at 0.5 MPa molten state, the titanium-based amorphous alloy was molten. Then, infiltration was performed at 0.5 MPa pressure to embed the molten titanium-based amorphous alloy into the silicon carbide framework. After holding at this temperature for 10 minutes, water quenching was performed to obtain a layered heterogeneous silicon carbide framework-titanium-based amorphous composite material. Its cross-sectional scanning electron micrograph is shown below. Figure 14 As shown.

[0083] The preparation method of the layered heterogeneous silicon carbide framework is as follows:

[0084] A three-dimensional framework structure was formed by alternately stacking monolayers of silicon carbide and monolayers of pure titanium mesh porous layers containing titanium particles. First, a thermal crosslinking treatment was performed at 220℃ for 6 hours. Then, a pyrolysis treatment was performed in an argon atmosphere at 0.3MPa, with the temperature increased to 1200℃ at 12℃ / min and held for 2 hours. Finally, a densification treatment was performed by hot isostatic pressing (HIP) at 1300℃ and 90MPa for 2 hours to obtain a densified layered heterogeneous silicon carbide framework.

[0085] The preparation method of a single-layer silicon carbide monolayer is as follows:

[0086] Silicon carbide powder and liquid polycarbosilane were mixed into a slurry, with the mass fraction of silicon carbide powder being 80%. After molding, a silicon carbide monolayer was obtained with a thickness of 400 μm.

[0087] The preparation method of a single-layer titanium mesh porous layer is as follows:

[0088] Pure titanium powder and polyvinyl alcohol were dispersed in deionized water to prepare an aqueous slurry. The aqueous slurry contained 35% pure titanium powder with a particle size of 1 μm and 15% polyvinyl alcohol. A 300 μm thick mesh film, namely a pure titanium mesh porous layer, was obtained by molding a polyurethane mesh with a pore size of 150 μm as a substrate.

[0089] The maximum compressive strength of the layered heterogeneous silicon carbide framework-titanium-based amorphous composite material containing titanium particles prepared in this embodiment is approximately 1550 MPa. When the notch is located in the amorphous alloy phase, the fracture toughness is 25.3 MPa·m. 1 / 2 When the notch is located in the silicon carbide phase, the fracture toughness is 18.0 MPa·m. 1 / 2 .

[0090] Example 5

[0091] In this layered heterogeneous silicon carbide framework-titanium-based amorphous composite material, the silicon carbide framework is composed of alternating layers of silicon carbide monolayers and silicon carbide mesh porous layers, and the silicon carbide framework contains silicon carbide particles with a particle size of 25 μm.

[0092] The specific preparation process of the composite material is as follows:

[0093] Layered heterogeneous silicon carbide framework and titanium-based bulk amorphous alloy ingot are placed in a mold and then subjected to 10... -3 Heating to 900℃ under vacuum at 0.3 MPa molten state, the titanium-based amorphous alloy was molten. Then, infiltration was performed at 0.3 MPa pressure to embed the molten titanium-based amorphous alloy into the silicon carbide framework. After holding at this temperature for 12 minutes, water quenching was performed to obtain a layered heterogeneous silicon carbide framework-titanium-based amorphous composite material. Its cross-sectional scanning electron micrograph is shown below. Figure 15 As shown.

[0094] The preparation method of the layered heterogeneous silicon carbide framework is as follows:

[0095] Alternating layers of single-layer silicon carbide monolayers and single-layer silicon carbide mesh porous layers are stacked to form a three-dimensional framework structure; first

[0096] The material was subjected to thermal crosslinking treatment at 200℃ for 5 hours, then heated to 850℃ at 10℃ / min in an argon atmosphere of 0.2MPa and held for 1.5 hours for pyrolysis treatment, and finally densified by hot isostatic pressing (HIP) at 1200℃ and 80MPa for 1.5 hours to obtain a densified layered heterogeneous silicon carbide framework.

[0097] The preparation method of a single-layer silicon carbide monolayer is as follows:

[0098] Silicon carbide powder and liquid polycarbosilane were mixed into a slurry, with the mass fraction of silicon carbide powder being 80%. After molding, a silicon carbide monolayer was obtained with a thickness of 100 μm.

[0099] The preparation method of a single-layer silicon carbide mesh porous layer is as follows:

[0100] Silicon carbide powder and polyvinyl alcohol were dispersed in deionized water to prepare an aqueous slurry. The aqueous slurry contained 28% silicon carbide powder with a particle size of 25 μm and 12% polyvinyl alcohol. A 100 μm thick mesh film, i.e., a silicon carbide mesh porous layer, was obtained by molding a polyurethane mesh with a pore size of 80 μm as a substrate.

[0101] The layered heterogeneous silicon carbide framework-titanium-based amorphous composite material prepared in this embodiment has a maximum compressive strength of approximately 1200 MPa. When the notch is located in the amorphous alloy phase, the fracture toughness is 13.5 MPa·m. 1 / 2 When the notch is located in the silicon carbide phase, the fracture toughness is 9.0 MPa·m. 1 / 2 .

[0102] Example 6

[0103] In this layered heterogeneous silicon carbide framework / titanium-based amorphous composite material, the silicon carbide framework is composed of alternating layers of silicon carbide monolayers and pure titanium mesh porous layers, and the silicon carbide framework contains titanium particles with a particle size of 25 μm.

[0104] The specific preparation process of the composite material is as follows:

[0105] A layered heterogeneous silicon carbide framework containing silicon carbide particles and a titanium-based bulk amorphous alloy ingot are placed in a mold and heated to 10°C. -3 Heating to 900℃ under vacuum at 0.3 MPa molten state, the titanium-based amorphous alloy was molten. Then, infiltration was performed at 0.3 MPa pressure to embed the molten titanium-based amorphous alloy into the silicon carbide framework. After holding at this temperature for 12 minutes, water quenching was performed to obtain a layered heterogeneous silicon carbide framework-titanium-based amorphous composite material. Its cross-sectional scanning electron micrograph is shown below. Figure 16 As shown.

[0106] The preparation method of the layered heterogeneous silicon carbide framework is as follows:

[0107] A three-dimensional framework structure was formed by alternately stacking monolayers of silicon carbide and monolayers of pure titanium mesh porous layers containing titanium particles. First, a thermal cross-linking treatment was performed at 200℃ for 5 hours. Then, a pyrolysis treatment was performed in an argon atmosphere at 0.2MPa, with the temperature increased to 850℃ at 10℃ / min and held for 1.5 hours. Finally, a densification treatment was performed by hot isostatic pressing (HIP) at 1200℃ and 80MPa for 1.5 hours to obtain a densified layered heterogeneous silicon carbide framework.

[0108] The preparation method of a single-layer silicon carbide monolayer is as follows:

[0109] Silicon carbide powder and liquid polycarbosilane were mixed into a slurry, with the mass fraction of silicon carbide powder being 80%. After molding, a silicon carbide monolayer was obtained with a thickness of 100 μm.

[0110] The preparation method of a single-layer pure titanium mesh porous layer is as follows:

[0111] Pure titanium powder and polyvinyl alcohol were dispersed in deionized water to prepare an aqueous slurry. The aqueous slurry contained 28% pure titanium powder with a particle size of 25 μm and 12% polyvinyl alcohol. A 100 μm thick mesh film, namely a pure titanium mesh porous layer, was obtained by molding a polyurethane mesh with a pore size of 80 μm as a substrate.

[0112] The maximum compressive strength of the layered heterogeneous silicon carbide framework-titanium-based amorphous composite material containing titanium particles prepared in this embodiment is approximately 1320 MPa. When the notch is located in the amorphous alloy phase, the fracture toughness is 21.3 MPa·m. 1 / 2 When the notch is located in the silicon carbide phase, the fracture toughness is 15.0 MPa·m. 1 / 2 .

[0113] Comparative Example 1

[0114] The main difference between Comparative Example 1 and Examples 1-6 is that the prepared composite material was not processed according to the optimized process parameters, as follows:

[0115] In this layered heterogeneous silicon carbide framework-titanium-based amorphous composite material, the silicon carbide framework is composed of alternating layers of silicon carbide monolayers and silicon carbide mesh porous layers. The silicon carbide framework contains silicon carbide particles with a particle size of 75 μm. The composite material contains 75% layered heterogeneous silicon carbide framework and 15% titanium-based amorphous alloy by volume, and 10% porosity.

[0116] The specific preparation process of the composite material is as follows:

[0117] A layered heterogeneous silicon carbide framework containing silicon carbide particles and a titanium-based bulk amorphous alloy ingot are placed in a mold and heated to 10°C. -3Heating to 800℃ under vacuum at 0.15 MPa molten state of the titanium-based amorphous alloy; then infiltration at 0.15 MPa molten state to embed the titanium-based amorphous alloy into the silicon carbide framework; after holding at this temperature for 8 minutes, water quenching is performed to obtain a layered heterogeneous silicon carbide framework-titanium-based amorphous composite material. Its cross-sectional scanning electron micrograph is shown below. Figure 17 As shown, there are obvious cracks.

[0118] The preparation method of the layered heterogeneous silicon carbide framework is as follows:

[0119] A three-dimensional framework structure was formed by alternately stacking monolayer silicon carbide sheets and monolayer silicon carbide mesh porous layers. First, a thermal cross-linking treatment was performed at 160℃ for 2 hours. Then, a pyrolysis treatment was performed in an argon atmosphere at 0.1MPa, with the temperature increased to 750℃ at 15℃ / min and held for 0.5 hours. Finally, a densification treatment was performed by hot isostatic pressing (HIP) at 1000℃ and 50MPa for 0.5 hours to obtain a densified layered heterogeneous silicon carbide framework.

[0120] The preparation method of a single-layer silicon carbide monolayer is as follows:

[0121] Silicon carbide powder and liquid polycarbosilane were mixed into a slurry, with the mass fraction of silicon carbide powder being 70%. After molding, a silicon carbide monolayer was obtained with a thickness of 100 μm.

[0122] The preparation method of a single-layer silicon carbide mesh porous layer is as follows:

[0123] Silicon carbide powder and polyvinyl alcohol were dispersed in deionized water to prepare an aqueous slurry. The aqueous slurry contained 40% silicon carbide powder with a particle size of 75 μm and 5% polyvinyl alcohol. A 100 μm thick mesh film, i.e., a silicon carbide mesh porous layer, was obtained by molding a polyurethane mesh with a pore size of 100 μm as a substrate.

[0124] The maximum compressive strength of the layered heterogeneous silicon carbide framework-titanium-based amorphous composite material prepared in this comparative example is approximately 420 MPa. When the notch is located in the amorphous alloy phase, the fracture toughness is 11.5 MPa·m. 1 / 2 When the notch is located in the silicon carbide phase, the fracture toughness is 8.0 MPa·m. 1 / 2 .

[0125] Comparative Example 2

[0126] The main difference between Comparative Example 2 and Examples 1-6 is that graphite particles were added to the prepared composite material, as detailed below:

[0127] In this layered heterogeneous silicon carbide framework-titanium-based amorphous composite material, the silicon carbide framework contains graphite particles and is composed of alternating layers of silicon carbide monolayers and graphite mesh porous layers. The graphite mesh porous layers contain graphite particles with a particle size of 85 μm. The composite material contains 75% layered heterogeneous silicon carbide framework and 18% titanium-based amorphous alloy by volume, and 7% porosity.

[0128] The specific preparation process of the composite material is as follows:

[0129] Layered heterogeneous silicon carbide framework and titanium-based bulk amorphous alloy ingot are placed in a mold and then subjected to 10... -3 Heating to 860℃ under vacuum at 0.3 MPa molten state, the titanium-based amorphous alloy was molten; then impregnated at 0.3 MPa pressure, held for 10 minutes, and then water-quenched to obtain a layered heterogeneous silicon carbide framework-titanium-based amorphous composite material containing graphite particles. Its cross-sectional scanning electron micrograph is shown below. Figure 18 As shown, there are obvious holes.

[0130] The preparation method of the layered isomeric silicon carbide framework containing graphite particles is as follows:

[0131] A three-dimensional framework structure was formed by alternately stacking single-layer silicon carbide monolayers and single-layer graphite mesh porous layers. First, it was subjected to thermal cross-linking treatment at 180℃ for 2 hours. Then, it was subjected to pyrolysis treatment by heating to 850℃ at 10℃ / min in an argon atmosphere of 0.3MPa and holding at that temperature for 1.5 hours. Finally, it was subjected to densification treatment by hot isostatic pressing (HIP) at 1250℃ and 85MPa for 1.5 hours to obtain a densified layered heterogeneous silicon carbide framework containing graphite particles.

[0132] The preparation method of a single-layer silicon carbide monolayer is as follows:

[0133] Silicon carbide powder and liquid polycarbosilane were mixed into a slurry, with the silicon carbide powder having a mass fraction of 75%. After molding, a silicon carbide monolayer was obtained with a thickness of 150 μm.

[0134] The preparation method of a single-layer graphite network porous layer is as follows:

[0135] A water-based slurry was prepared by dispersing graphite powder and polyvinyl alcohol in deionized water. The water-based slurry contained 35% graphite powder by mass, 99.8% purity, and 85μm particle size, and 8% polyvinyl alcohol by mass. A 100μm thick mesh film, i.e., a graphite mesh porous layer, was obtained by molding a polyurethane mesh with a pore size of 145μm as a substrate.

[0136] The maximum compressive strength of the layered heterogeneous silicon carbide framework-titanium-based amorphous composite material containing graphite particles prepared in this comparative example is approximately 256 MPa. When the notch is located in the amorphous alloy phase, the fracture toughness is 8.5 MPa·m.1 / 2 When the notch is located in the silicon carbide phase, the fracture toughness is 6.0 MPa·m. 1 / 2 .

[0137] Comparative Example 3

[0138] The main difference between Comparative Example 3 and Examples 1-6 is that the silicon carbide framework in the prepared composite material is a porous continuous framework, as detailed below:

[0139] In this porous silicon carbide framework-titanium-based amorphous composite material, the silicon carbide framework has a porous structure and is formed by mixing and sintering silicon carbide powder, alumina powder and yttrium oxide powder. The composite material contains 60% porous silicon carbide framework and 40% titanium-based amorphous alloy by volume.

[0140] The specific preparation process of the composite material is as follows:

[0141] A porous silicon carbide framework and a titanium-based bulk amorphous alloy ingot are placed in a mold, and then... -3 Heating to 850℃ under vacuum at 0.3 MPa molten state, the titanium-based amorphous alloy was molten. Then, infiltration was performed at 0.3 MPa pressure to embed the molten titanium-based amorphous alloy into the silicon carbide framework. After holding at this temperature for 13 minutes, water quenching was performed to obtain a porous silicon carbide framework-titanium-based amorphous composite material. Its cross-sectional scanning electron micrograph is shown below. Figure 19 As shown, there are obvious blocky protrusions.

[0142] The preparation method of the porous silicon carbide framework is as follows:

[0143] Silicon carbide powder, alumina powder, and yttrium oxide powder were formulated into a mixed powder and ball-milled. The mixed powder contained 90% silicon carbide powder with a particle size of 30 μm, 5% alumina powder with a particle size of 1 μm, and 5% yttrium oxide powder with a particle size of 5 μm. The purity of all powders was 99.99%. The ball-milled mixed powder was placed in a hot press mold and sintered at 1850℃, 45 MPa, and an argon atmosphere for 1.5 hours to obtain a porous silicon carbide framework.

[0144] The porous silicon carbide framework-titanium-based amorphous composite material prepared in this comparative example has a maximum compressive strength of approximately 1256 MPa and a fracture toughness of 5.5 MPa·m. 1 / 2 .

[0145] Matters not covered in this invention are common knowledge.

[0146] The above embodiments are only for illustrating the technical concept and features of the present invention, and are intended to enable those skilled in the art to understand the content of the present invention and implement it accordingly. They should not be construed as limiting the scope of protection of the present invention. All equivalent changes or modifications made in accordance with the spirit and essence of the present invention should be covered within the scope of protection of the present invention.

Claims

1. A method for preparing a layered heterogeneous silicon carbide framework-titanium-based amorphous composite material, characterized in that, The specific steps include: placing a silicon carbide skeleton and a titanium-based amorphous alloy in a mold, heating it to 860℃~950℃ in a vacuum environment to make the titanium-based amorphous alloy molten, and then holding it at a pressure of 0.3MPa~0.5MPa for 10 to 15 minutes to allow the molten titanium-based amorphous alloy to infiltrate and embed into the silicon carbide skeleton. After water quenching and cooling, a layered heterogeneous silicon carbide skeleton-titanium-based amorphous composite material is obtained. The method for preparing the silicon carbide framework is as follows: at least one of a single-layer silicon carbide mesh porous layer and a single-layer titanium mesh porous layer is alternately stacked with a single-layer silicon carbide monolayer to form a three-dimensional framework structure. The silicon carbide framework was obtained after thermal crosslinking, pyrolysis, and densification treatment. The thermal crosslinking treatment refers to holding at 180℃~220℃ for 4 to 6 hours; the pyrolysis treatment refers to heating to 850℃~1200℃ at 8℃ / min~12℃ / min in an argon atmosphere of 0.2MPa~0.4MPa and holding for 1 to 2 hours; the densification treatment refers to hot isostatic pressing at 1200℃~1400℃ and 80MPa~100MPa for 1 to 2 hours. The preparation method of the single-layer silicon carbide monolayer is as follows: silicon carbide powder and liquid polycarbosilane are mixed into a slurry, and the single-layer silicon carbide monolayer is obtained after molding; the mass fraction of silicon carbide powder in the mixed slurry is 80%; The preparation method of the single-layer silicon carbide mesh porous layer is as follows: silicon carbide powder and polyvinyl alcohol are formulated into an aqueous slurry M, which is then molded in a polyurethane mesh substrate to obtain the single-layer silicon carbide mesh porous layer; the mass fraction of silicon carbide powder in the aqueous slurry M is 20%~35%, and the mass fraction of polyvinyl alcohol is 10%~15%. The preparation method of the single-layer titanium mesh porous layer is as follows: titanium powder and polyvinyl alcohol are dispersed in deionized water to prepare an aqueous slurry N, which is then formed in a polyurethane mesh substrate to obtain the single-layer titanium mesh porous layer; the mass fraction of titanium powder in the aqueous slurry N is 20%~35%, and the mass fraction of polyvinyl alcohol is 10%~15%.

2. The method for preparing a layered heterogeneous silicon carbide framework-titanium-based amorphous composite material according to claim 1, characterized in that, The thickness of the single-layer silicon carbide sheet is 100μm~400μm, the pore size of the polyurethane mesh substrate is 80μm~150μm, the thickness of the single-layer silicon carbide mesh porous layer is 100μm~300μm, and the thickness of the single-layer titanium mesh porous layer is 100μm~300μm.

3. A layered heterogeneous silicon carbide framework-titanium-based amorphous composite material obtained by the preparation method according to claim 1, characterized in that, The composite material is composed of a silicon carbide skeleton and a titanium-based amorphous alloy, wherein the titanium-based amorphous alloy is infiltrated and embedded in the silicon carbide skeleton; the silicon carbide skeleton is a multilayer heterogeneous structure, consisting of at least one of a single-layer silicon carbide mesh porous layer and a single-layer titanium mesh porous layer, which are alternately stacked with single-layer silicon carbide monolayers.

4. The layered heterogeneous silicon carbide framework-titanium-based amorphous composite material according to claim 3, characterized in that, The silicon carbide framework contains silicon carbide particles with a particle size of 500 nm to 50 μm or titanium particles with a particle size of 1 μm to 50 μm.